ESTUDIOS TRANSATLáNTICOS COMO UN NUEVO RETO PARA LOS ESTUDIOS LATINOAMERICANOS - Dembicz, Katarzyna (2015)
Considering that the paradigm of regionalstudies is no longer sufficient to cover thespace in which Latin American studies areperformed, with this paper would try tocontribute to the debate on the potential of anew, transatlantic perspective. However, thisshould regard on various levels of scientificactivity: research, documentation, educationand information, as it has been done so far inthe context of Latin American studies.The increasing interregional relationsmake of transatlantic studies a good approach.This is already happening, as several centersin Europe and the United States have creatednew opportunities for research, analysisand teaching. But we need a broad discussionabout it, about the definition and methodologyof transatlantic studies.